Performance Evaluation of Power Weeder with Different Blade Mechanism in Intra-row Weeding Operation - Shadad Md Khayer; Thaneswer Patel; Britan Rahman; Perves Ahmed (Archives of Current Research International, 2024)
Aims: Weeding operation is one of the most laborious and time-consuming operation in agriculture. Weeds basically an unwanted plant which competes with crop for light, moisture, and nutrient along with lowering the overall yield. Mechanical weed control methods are preferred among all weeding methods due to many reasons such as timeliness, safety, drudgery and cost effective. Study Area and Duration: The experiment was conducted in the farmer’s field of Abhayapuri, Bongaigaon, Assam in the year 2021 to 2023. Methodology: This study employed a 5.75 hp self-propelled diesel engine with three blade sets—rotary, non-rotary, and a combination of both, designed for weeding in vegetable fields with row spacing up to 75 cm. One-way ANOVA analysis compared group means for statistical significance. Results: Results showed that the field efficiency (90%), fuel consumption (7.7 l/ha), cost of operation (Rs 1217.7 per ha) and plant damage factor (0.01%) was better for rotary blade than non-rotary and combined blade. Whereas effective field capacity (0.07 ha/h), performance index (155.7) and man-hour/ha (14.3) was better for non-rotary blade and the parameters such as depth (4.4 cm) and weeding efficiency (94.2%) was better for combined blade mechanism. From the one-way ANOVA analysis, it showed that blade mechanism showed significant difference on parameters like weeding efficiency, field efficiency, fuel consumption, effective field capacity, cost of operation, man-h/ha and performance index at p<0.05 and non-significant for depth and plant damage factor at P<0.05. Conclusion: Study concluded that for intra-row weeding operation, rotary blade along with non-rotary blade was suitable economically whereas combined blade was suitable for weeding performance only besides high cost.